Critical and Reflective Analysis of the Evolution of the Audit Process in the Digital Age - Andi Nurul Azizah; Detri Heri Gumita; Zuhalwah Yuliah Ilham; Amiruddin Amiruddin (International Journal of Economics Development Research (IJEDR), 2025)
Analysing the evolution of the audit process in the digital era, evaluating the implications of technology on methodology, quality, auditor competence, ethics, and the effectiveness of internal controls, with a focus on opportunities and challenges in developing countries. A Systematic Literature Review (SLR) of 29 articles (2015-2025) from Scopus, ScienceDirect, Publish and Pearish, and Google Scholar using thematic analysis to identify patterns, contradictions, and trends. Technologies such as AI, Big Data, Blockchain, RPA, and Continuous Auditing are transforming auditing into an automated, real-time, and predictive model, increasing efficiency and reducing costs. Risks include algorithmic bias, lagging regulations, and the need to transform the role of auditors into strategic advisors with digital competencies. Recommendations include strengthening auditor competencies through digital education, regulatory adaptation, and RPA implementation in developing countries to maintain audit relevance, improve governance, and stakeholder confidence in financial reporting. A multidimensional critical-reflective approach that integrates technology, profession, control, and ethics with a unique focus on the context of developing countries.